Nerve growth factor receptor is involved in maintaining homeostasis of pulmonary arterial hypertension. (25th November 2020) - Goten, C; Usui, S; Inoue, O; Okada, H; Takashima, S; Sakata, K; Kawashiri, M; Takamura, M
Abstract: Introduction: Pulmonary arterial hypertension (PAH), characterized by vascular remodeling, is still disease with poor prognosis although many pulmonary vasodilators have been developed, and new mechanism of treatment for PAH is desired. Nerve growth factor receptor (Ngfr) is known to relate to inflammatory reaction and repair process in the damaged tissue. We have reported that Ngfr is associated to vascular remodeling in patients with acute coronary syndrome. However, it is unclear how Ngfr is involved in the pathogenesis of PAH. Purpose: In this study, we investigated whether Ngfr relate to pathophysiology in PAH. Methods: We estimated the frequency of Ngfr positive cells (% Ngfr+) in peripheral blood mononuclear cells obtained from PAH and non-PAH patients using flowcytometric analysis. In PAH patients, the hemodynamic parameters such as mean pulmonary arterial pressure (mPAP), pulmonary vascular resistance (PVR), and cardiac index (CI) were obtained by right heart catheterization, and evaluated for correlation with the % Ngfr+. Next, adult 8-week-old C57BL/6 (WT) mice and Ngfr knock out (KO) mice were exposed to chronic hypoxia (10% O2) or normoxia for 6 weeks. Then, mice were anesthetized and performed echocardiography and right heart catheterization. Then, mice were exsanguinated and blood sample was collected to evaluate the % Ngfr+ by flow cytometry. Right ventricular weight was measured and lung tissue was also collected for histological assessment and molecular pathway profiling. Results: PAH (n=24) patients and non-PAH patients (n=17) were enrolled. The % Ngfr+ was significantly higher in PAH patients than that in non-PAH patients (0.056% versus 0.019%, p<0.0001). In PAH patients, the % Ngfr+ was correlated with severity of hemodynamic parameters such as mPAP (R=0.64 p<0.001), PVR (R=0.62 p<0.005), and CI (R=−0.48 p<0.05). In WT mice, chronic hypoxia significantly increased the right ventricular systolic pressure and induced vascular medial thickness and fibrosis around the pulmonary artery. Flow cytometry analysis revealed that the % Ngfr+ was significantly increased in the hypoxia compared to that in the normoxia. Under hypoxic conditions, the right ventricular systolic pressure was significantly increased in Ngfr KO mice compared to that in WT mice. In histological analysis, hypoxia-induced peripheral vascular fibrosis and medial thickness was more severe in Ngfr KO than that in WT mice. Conclusion: Circulating Ngfr-positive cells are associated with severity of PAH in patients. In the hypoxia-induced PH model, gene deletion of Ngfr shows the progression of the pathogenesis of PAH. These results suggest that circulating Ngfr-positive cells have an important role in the pathogenesis of PAH and may be a novel target for PAH therapy. Funding Acknowledgement: Type of funding source: None